2020 IEEE 27th International Conference on Software Analysis, Evolution and Reengineering (SANER) 2020
DOI: 10.1109/saner48275.2020.9054812
|View full text |Cite
|
Sign up to set email alerts
|

Unleashing the Potentials of Immersive Augmented Reality for Software Engineering

Abstract: In immersive augmented reality (IAR), users can wear a head-mounted display to see computer-generated images superimposed to their view of the world. IAR was shown to be beneficial across several domains, e.g., automotive, medicine, gaming and engineering, with positive impacts on, e.g., collaboration and communication. We think that IAR bears a great potential for software engineering but, as of yet, this research area has been neglected. In this vision paper, we elicit potentials and obstacles for the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, most papers [41,57,58] referring to the potential use of VR and AR for the workspace of software development teams. In general, the use of VR and AR in software engineering is not well studied yet, and the only papers available or mainly vision papers for future research [44]. However, in our work, we present a practical application of VR for assessing the test oracles with a Human-in-the-Loop approach.…”
Section: Immersion Technology In Software Engineeringmentioning
confidence: 99%
“…Furthermore, most papers [41,57,58] referring to the potential use of VR and AR for the workspace of software development teams. In general, the use of VR and AR in software engineering is not well studied yet, and the only papers available or mainly vision papers for future research [44]. However, in our work, we present a practical application of VR for assessing the test oracles with a Human-in-the-Loop approach.…”
Section: Immersion Technology In Software Engineeringmentioning
confidence: 99%
“…Navigation and occlusion in particular pose fewer problems in AR. The authors also found that software comprehension tasks with 3D software visualizations could be solved more effective with AR devices than standard computer screens and identified great potential of AR for software engineering [4]. Nevertheless, software analytics is hardly ever done in AR and in our own experience many software developers approach this topic with reservations.…”
Section: Introductionmentioning
confidence: 99%